Aromaterapi Jahe Efektif menurunkan Post Operative Nausea and Vomiting pada Pasien Post General Anestesi di RSUD Kanjuruhan - Asriani, Nilam Suci; Yuswanto, Tri Johan Agus Agus; Arif, Taufan (FORIKES, 2023)
General anesthesia can cause side effects such as post operative nausea and vomiting. This study aims to determine which is more effective between early mobilization and ginger aromatherapy for post operative nausea and vomiting in post general anesthesia patients at Kanjuruhan Hospital B. The research method used was